Making things and drawing boundaries : experiments in the digital humanities - Sayers, Jentery, 1978- (Debates in the digital humanities., 2017)
In Making Things and Drawing Boundaries, critical theory and cultural practice meet creativity, collaboration, and experimentation with physical materials as never before. Foregrounding the interdisciplinary character of experimental methods and hands-on research, this collection asks what it means to makethings in the humanities. How is humanities research manifested in hand and on screen alongside the essay and monograph? And, importantly, how does experimentation with physical materials correspond with social justice and responsibility? Comprising almost forty chapters from ninety practitioners across twenty disciplines, Making Things and Drawing Boundaries speaks directly and extensively to how humanities research engages a growing interest in makerculture, however making may be defined.